Creditors and dividend policy: Reputation building versus debt covenant - Quoc Trung Tran (European Research on Management and Business Economics (ERMBE), 2019)
Agency problem between shareholders and creditors can be reduced by two mechanisms namely reputation-building and debt covenant. Prior studies document supporting evidence for both hypotheses with a positive relationship between creditor rights and dividend policy. However, they fail to test reputation-building mechanism and debt covenant mechanism separately. This paper finds that credit information and legal rules supporting moveable assets are promising variables to fill this gap since the two mechanisms provide opposite effects of credit information and legal rules on dividend policy. With a sample of 37,673 observations collected across 39 countries over the period from 2013 to 2015 we find supporting evidence for debt covenant hypothesis and creditor information has a complementary effect on legal rules in determining corporate dividend policy.
Keywords: 650; Creditors; Dividend policy; Reputation building; Debt covenant